2017
DOI: 10.1039/c7bm00108h
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial nitric oxide releasing surfaces based on S-nitroso-N-acetylpenicillamine impregnated polymers combined with submicron-textured surface topography

Abstract: A novel dual functioning antimicrobial CarboSil 20 80A polymer material that combines physical topographical surface modification and nitric oxide (NO) release is prepared and evaluated for its efficacy in reducing bacterial adhesion in vitro. The new biomaterial is created via a soft lithography two-stage replication process to induce submicron textures on its surface, followed by solvent impregnation of the NO donor, S-nitroso-N-acetylpenicillamine (SNAP), to obtain long-term (up to 38 d) of NO release. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 52 publications
(56 reference statements)
0
39
1
Order By: Relevance
“…NO releasing materials may be ideal candidates for the development of novel biomedical devices which can effectively prevent bacterial infection and thrombus formation, since NO is identified to be capable of preventing platelet activation and adhesion, and inhibiting bacterial proliferation and biofilm formation [109]. S -Nitroso- N -acetylpenicillamine (SNAP), a commonly used nitrosothiol typed NO donor, has been extensively investigated to incorporate into biomedical grade polymers to create NO releasing materials [159,160,161,162,163] because of its low cost, safety, stability during release and storage, demonstrating the potential for long-term applications [164]. Meyerhoff and Handa et al prepared NO releasing catheters by doping SNAP into the Elast-Eon E2As polymers [67].…”
Section: No Releasing Polymers Applied In Indwelling Medical Devicesmentioning
confidence: 99%
“…NO releasing materials may be ideal candidates for the development of novel biomedical devices which can effectively prevent bacterial infection and thrombus formation, since NO is identified to be capable of preventing platelet activation and adhesion, and inhibiting bacterial proliferation and biofilm formation [109]. S -Nitroso- N -acetylpenicillamine (SNAP), a commonly used nitrosothiol typed NO donor, has been extensively investigated to incorporate into biomedical grade polymers to create NO releasing materials [159,160,161,162,163] because of its low cost, safety, stability during release and storage, demonstrating the potential for long-term applications [164]. Meyerhoff and Handa et al prepared NO releasing catheters by doping SNAP into the Elast-Eon E2As polymers [67].…”
Section: No Releasing Polymers Applied In Indwelling Medical Devicesmentioning
confidence: 99%
“…As a prominent gasotransmitter, NO has been demonstrated to influence abundant physiological processes including cell apoptosis, angiogenesis, immune responses, neurotransmission, etc . Therefore, NO has been extensively explored in versatile biomedical applications such as cardiovascular homeostasis, bone metabolism and neurotransmission, respiratory diseases, antimicrobial therapy, wound healing, and antibacterial . Especially, NO can efficiently kill the cancer cells via the nitrosation of mitochondria and DNA, paving the new way for NO‐induced cancer therapy .…”
Section: Nitric Oxide (No)‐generating Ggnsmentioning
confidence: 99%
“…The textured PU film surfaces with ordered arrays of pillars were prepared by a modified soft lithography two-stage replication molding technique and impregnated with SNAP as described previously. [30] Briefly, a PDMS mold was obtained by casting against the Si wafer with the pattern of 700/700/300 nm and cured at 65°C under vacuum for 6 hrs to provide a negative silicone mold. A CarboSil PU solution was then spin-coated onto the silicon mold to prepare the textured PU films.…”
Section: Preparation Of Biomimetic Pu Films With Surface Texturing and No Releasementioning
confidence: 99%
“…Toward this goal, we recently created a dual functional surface with a combination of surface texturing and NO release integrated on PU biomaterials, where S-nitroso-Nacetylpenicillamine (SNAP) was used as the NO donor within the PU and the surface was textured with submicron pillar patterns (Scheme 1). [29,30] Results showed that the combination of surface texturing and NO release synergistic or additively reduced bacterial adhesion and inhibited biofilm formation. Moreover, utilizing an impregnation of SNAP in the polymer led to NO release at a stable and long term NO release for up to 38 days for 15% SNAP load, far longer than the NO release lifetime using a SNAP-doped PU with same amount of SNAP load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation